2022
DOI: 10.1021/acs.jpclett.2c02717
|View full text |Cite
|
Sign up to set email alerts
|

TiO2 as a Nanozyme Mimicking Photolyase to Repair DNA Damage

Abstract: Cyclobutane pyrimidine dimer (CPD) is the most abundant DNA photolesion, and it can be repaired by photolyases based on electron-transfer mechanisms. However, photolyase is absent in the human body and lacks stability for applications. Can one develop natural enzyme mimetics utilizing nanoparticles (termed nanozymes) to mimic photolyase in repairing DNA damage? Herein, we observe the successful reversal of thymine dimer T<>T to normal T base by TiO2 under UVA irradiation. Time-resolved spectroscopy provides di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…For instance, we found that adding a small amount of GeO2 powders into the reaction solution signif- There are a wide variety of compounds in the plant leaf ashes; some of them could be potential efficiency photocatalysts. The existence of different ions may also promote photocatalytic activity, as mentioned in the literature [60,61]. Very interestingly, after the washing of the ashes, the decrease in the photodegradation yield proved the promotion roles of soluble ions in ashes (Figure 3).…”
Section: Preparation and Characterization Of Different Plant Leavesmentioning
confidence: 63%
“…For instance, we found that adding a small amount of GeO2 powders into the reaction solution signif- There are a wide variety of compounds in the plant leaf ashes; some of them could be potential efficiency photocatalysts. The existence of different ions may also promote photocatalytic activity, as mentioned in the literature [60,61]. Very interestingly, after the washing of the ashes, the decrease in the photodegradation yield proved the promotion roles of soluble ions in ashes (Figure 3).…”
Section: Preparation and Characterization Of Different Plant Leavesmentioning
confidence: 63%